Effects of immediate versus gradual nicotine reduction in cigarettes on biomarkers of biological effects. (8th July 2019) - Hatsukami, Dorothy K.; Luo, Xianghua; Heskin, Alisa K.; Tang, Mei Kuen; Carmella, Steven G.; Jensen, Joni; Robinson, Jason D.; Vandrey, Ryan; Drobes, David J.; Strasser, Andrew A.; al'Absi, Mustafa; Leischow, Scott; et al.
Abstract: Aim: A previous study showed significantly greater reductions in number of cigarettes smoked and biomarkers of toxicant and carcinogen exposure in smokers assigned to immediate reduction of nicotine in cigarettes to very low levels versus gradually over time or continued smoking of normal nicotine content cigarettes. This study examines the effects of these approaches on selected biomarkers associated with harmful biological effects. Design: Three‐arm, randomized controlled trial. Setting: Ten United States academic institutional sites. Participants: Daily smokers uninterested in quitting smoking with a mean age of 45.1 [standard deviation (SD) = 13.4)] years and smoking 17.1 (SD = 8.5) cigarettes/day; 43.9% (549 of 1250) female; 60.6% (758 of 1250) white ethnicity. Interventions: (1) Smoking cigarettes where nicotine content was immediately reduced to very low levels ( n  = 503); (2) smoking cigarettes where nicotine content was gradually reduced, with dose changes occurring monthly ( n  = 498); and (3) continued smoking with normal nicotine content cigarettes ( n  = 249). Measurements: Smokers were assessed at baseline while smoking their usual brand cigarettes, and again at 4, 8, 12, 16 and 20 weeks. Outcomes were areas under the concentration time curve (AUC) for the period of study of biomarkers of inflammation, oxidative stress and hematological parameters. Findings: No consistent significant differences were observed across groups (Bayes factors showing data to be insensitive), with the only exception being red blood cell size variability, which was observed to be lower in the immediate versus gradual nicotine reduction [mean difference =  −0.11; 95% confidence interval (CI) = –0.18, −0.04, P  = 0.004] and normal nicotine control groups (mean difference = − 0.15, 95% CI = –0.23, −0.06, P  = 0.001). Conclusion: It remains unclear whether switching to very low nicotine cigarettes leads to a short‐term reduction in biomarkers of tobacco‐related harm.